2009
DOI: 10.1074/jbc.m109.017681
|View full text |Cite
|
Sign up to set email alerts
|

Cdc2-mediated Phosphorylation of CLIP-170 Is Essential for Its Inhibition of Centrosome Reduplication

Abstract: CLIP-170, the founding member of microtubule "plus ends tracking" proteins, is involved in many critical microtubulerelated functions, including recruitment of dynactin to the microtubule plus ends and formation of kinetochore-microtubule attachments during metaphase. Although it has been reported that CLIP-170 is a phosphoprotein, neither have individual phosphorylation sites been identified nor have the associated kinases been extensively studied. Herein, we identify Cdc2 as a kinase that phosphorylates CLIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The mutation of Ser312 to alanine markedly reduced CLIP-170 phosphorylation by Plk1 but not by Cdk1 ( Fig. 2A), indicating that Cdk1 phosphorylates other residue(s), including Thr287 as previously reported (Yang et al, 2009). Immunoblot analysis with the anti-phosphorylated CLIP-170 antibody further demonstrated that Plk1 indeed phosphorylated Ser312 (Fig.…”
Section: Plk1 Phosphorylates Clip-170 At Ser312 In Vitrosupporting
confidence: 82%
See 1 more Smart Citation
“…The mutation of Ser312 to alanine markedly reduced CLIP-170 phosphorylation by Plk1 but not by Cdk1 ( Fig. 2A), indicating that Cdk1 phosphorylates other residue(s), including Thr287 as previously reported (Yang et al, 2009). Immunoblot analysis with the anti-phosphorylated CLIP-170 antibody further demonstrated that Plk1 indeed phosphorylated Ser312 (Fig.…”
Section: Plk1 Phosphorylates Clip-170 At Ser312 In Vitrosupporting
confidence: 82%
“…Recent studies have demonstrated that CLIP-170 is indeed phosphorylated and successfully identified the responsible kinases (Yang et al, 2009;Lee et al, 2010;Li et al, 2010;Nakano et al, 2010). We previously found that AMPK .…”
Section: Clip-170 Phosphorylation and Its Kinasesmentioning
confidence: 97%
“…Both phosphorylation events are required for the dynactin-dependent kinetochore localization of CLIP-170 and the formation of KT-MT attachments (Li et al, 2010). Moreover, CLIP-170 is phosphorylated on T287 by cyclin-dependent kinase 1 (CDK1) -an event that is essential for cell cycle progression (Yang et al, 2009). However, the mechanism of the role of CLIP-170 in chromosome alignment remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CLIP-170 can be phosphorylated on multiple residues (Rickard and Kreis, 1991;Choi et al, 2002;Yang et al, 2009). Previous studies have demonstrated that CLIP-170 is phosphorylated in the third serine-rich region adjacent to the second CAP-Gly microtubule-binding domain (Lee et al, 2010;Nakano et al, 2010).…”
Section: Discussionmentioning
confidence: 99%